2013
DOI: 10.1590/0004-282x20130021
|View full text |Cite
|
Sign up to set email alerts
|

Tonic spasms are a common clinical manifestation in patients with neuromyelitis optica

Abstract: Tonic spasms have been most commonly associated with multiple sclerosis. To date, few reports of series of patients with neuromyelitis optica and tonic spasms have been published.Methods:We analyzed the characteristics and frequency of tonic spasms in 19 subjects with neuromyelitis optica. Data was collected using a semi-structured questionnaire for tonic spasms, by both retrospectively reviewing medical records and performing clinical assessment.Results:All patients except one developed this symptom. The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
1
12
0
4
Order By: Relevance
“…In our experience, in a recent study, we found the presence of paroxysmal dystonia in 95 % (18 of 19) of a group of patients with clinical and radiological criteria for NMO spectrum disorders [4]. The principal features of our patients were the occurrence of a somesthetic aura associated with the paroxysmal dystonia in 18 of 19 patients, as well as the worsening of the movement disorders during the acute phases of the disease.…”
supporting
confidence: 46%
“…In our experience, in a recent study, we found the presence of paroxysmal dystonia in 95 % (18 of 19) of a group of patients with clinical and radiological criteria for NMO spectrum disorders [4]. The principal features of our patients were the occurrence of a somesthetic aura associated with the paroxysmal dystonia in 18 of 19 patients, as well as the worsening of the movement disorders during the acute phases of the disease.…”
supporting
confidence: 46%
“…Previous studies of movement disorders in NMO have focused mainly on tonic spasms where prevalence ranged from 14% to 95%. 16,17 Our data come in the midpoint of this wide range with a prevalence rate of 43.2% for any SMD and 35% for tonic spasms. We realize that our cohort of patients requiring admission and plasmapharesis may represent the more severe end of the NMO spectrum, where SMDs may be over-represented compared to patients with milder disease course.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies of movement disorders in NMO have focused mainly on tonic spasms where prevalence ranged from 14% to 95% . Our data come in the midpoint of this wide range with a prevalence rate of 43.2% for any SMD and 35% for tonic spasms.…”
Section: Discussionmentioning
confidence: 99%
“…TS have been noted in demyelinating diseases, sometimes presenting as initial symptom (Matthews 1958, Muto, Mori et al 2015; TS can occur in 4-17% of MS patients (Matthews 1958, Kuroiwa and Araki 1963, Shibasaki and Kuroiwa 1974, Matthews 1975. In NMO / NMOS patients it can occur more often (14-95%) (Wingerchuk, Hogancamp et al 1999, Kim, Go et al 2012, Usmani, Bedi et al 2012, Abaroa, Rodriguez-Quiroga et al 2013.…”
Section: Tonic Spasmsmentioning
confidence: 99%
“…have been reported ). Several reports, often accidental case reports, on other NMO symptoms such as narcolepsy, hypothermia, hearing loss, severe pain, tonic spasms, neuropathic pruritus etc can also be found, thought whether they are characteristic for NMO is yet to be studied (Baba, Nakashima et al 2009, Kanbayashi, Shimohata et al 2009, Sato and Fujihara 2011, Suzuki, Nakamura et al 2012, Nakano, Dei et al 2014,Jarius, Lauda et al 2013, Gratton, Amjad et al 2014, Takanashi, Misu et al 2014, El Otmani, Dany et al 2015, Wang, Qi et al 2015, Wingerchuk, Hogancamp et al 1999, Kim, Go et al 2012, Usmani, Bedi et al 2012, Abaroa, Rodriguez-Quiroga et al 2013.…”
Section: Introductionmentioning
confidence: 99%